A taxonomic report on the cockroach genus Haplosymploce Hanitsch from China including one new species (Blattodea: Ectobiidae: Blattellinae) - Zheng, Yuhong (Zootaxa, 2016)
The cockroach genus Haplosymploce Hanitsch is recorded from China for the first time with two species: H. andamanica (Princis, 1951) from Yunnan which was originally recorded from Andaman, and H. aurantiaca sp. n. from Hainan, a phototactic species remarkable by the orangish yellow cerci, it is very likely to be a wood-feeding species and thus, along with the genus, stands out among Ectobiidae (=Blattellidae). Male of both and female of H. aurantiaca sp. n. are described, illustrated and photographed; the female genitalia of the new species show a high degree of asymmetry. Photos of H. aurantiaca sp. n. in the wild are provided, as well as a key to the males of 8 out of 11 known species worldwide.